Study on the cultivation of Lactobacillus using rice wine lees and protection capabilities during spray and freeze drying - Liya Tian; Xing Wang; Qingyun Lyu; Lijie Zhu; Lei Chen; Xi Chen; Wenping Ding (Food Chemistry: X)
Rice wine lees (RWL), a byproduct of traditional Chinese rice wine production, can be used to cultivate Lactobacillus strains and enhance their viability during spray drying (28.5 % survival) and freeze drying (31.8 % survival). Spray-dried powders exhibited uniform spherical morphology, smaller particle size, and improved gastric tolerance, while freeze-dried samples retained greater odour diversity, as confirmed by GC-IMS analysis. Electronic nose analysis indicated reduced volatile compounds in spray-dried probiotics. Both drying methods produced powders stable at 4 °C and 20 °C for two months, maintaining viable counts above 107 CFU/g. These findings highlight the potential of RWL to improve processing adaptability and storage stability of microbial formulations, offering an eco-friendly substrate for probiotic applications.